Real Time Monitoring the Maillard Reaction Intermediates by HPLC- FTIR - Ioannou, Aristos; Varotsis, Constantinos (My University, 2016)
Maillard reaction products in the food-, nutrition- and pharmaceutical related processes are of great interest in cases where the substances involved are chemically reactive or unstable. Detailed data using vibrational FTIR spectroscopy of the Maillard-type reaction products are limited and needs more experimental evidences with explicit mechanisms of the reaction to demonstrate how the reducing sugars be avoided in formulating the amine-containing substances. The combination of high performance liquid chromatography (HPLC) with Fourier transform infrared (FTIR) spectrometry is a powerful instrumental separation-structure sensitive technique that allows characterization in real time of the separated chemical species. In this short review we demonstrate the benefits of the HPLC-FTIR coupling technique in studying the Maillard reaction model Fructose/Asparagine system.
Keywords: Maillard reaction; Asparagine; Fructose; HPLC- ATRFTIR